Genetically modified food and global warfare - Carter, Colin Andre; Moschini, Giancarlo; Sheldon, Ian M. (Bingley, U.K. : Emerald, 2011)
Genetically modified (GM) (or transgenic) crops are produced using plant biotechnology to select desirable characteristics in plants and transfer genes from one organism to another. As a result, crops can survive under harsher conditions, costs are lowered, chemical application is reduced, and yields are improved. Scientists are introducing genes into plants that will give them resistance to herbicides, insects, disease, drought and salt in the soil. The application of modern biotechnology to crop and food production is one of the most significant technological advances to impact modern agriculture. The future of GM technology holds further promises of continued benefits. But the potential of GM product innovations has been overshadowed by significant controversy over this technology. The regulatory activism that has accompanied the diffusion of GM technology has given rise to a complex situation that is replete with obstacles for current and future GM innovations. This is particularly true for the European Union (EU), which has implemented restrictive policies that undoubtedly constrain the current status and the future potential of biotechnology. The discourse on biotechnology applied to food and agriculture is at a crossroads due to rising food prices and concerns about adequate food supplies and limited land and water. Over the last decade a large body of applied economics work has addressed the key questions surrounding the application of this technology to food production. It is now time to take stock of the results of these efforts, and consolidate the methodological, analytical and empirical findings. The challenge is to strengthen the consensus of what economics has to offer in the analysis of the complex issues surrounding the ongoing development of GM products for the agricultural and food sector. The motivation for this volume is to provide a new perspective on the most pressing policy questions regarding GM crops and to help foster an intellectual climate conducive to achieving meaningful progress and lasting solutions. It brings together fresh insights from top agricultural economists in the areas of consumer attitudes, environmental impacts, policy and regulation, trade, investment, food security, and development.
Introduction / Colin A. Carter, GianCarlo Moschini, Ian Sheldon -- ch. 1. Biotechnology and agriculture : current and emerging applications / Robert W. Herdt, Rebecca Nelson -- ch. 2. Genetically modified crops and global food security / Matin Qaim -- ch. 3. Current and potential farm-level impacts of genetically modified crops in developing countries / Terri Raney, Ira Matuschke -- ch. 4. The impact of Bt cotton and the potential impact of biotechnology on other crops in China and India / Carl E. Pray, Latha Nagarajan, Jikun Huang, Ruifa Hu, Bharat Ramaswami -- ch. 5. Contributions of public and private R&D to biotechnology innovation / Wallace E. Huffman -- ch. 6. Spatial pricing of genetically modified hybrid corn seeds / Kyle W. Stiegert, Guanming Shi, Jean-Paul Chavas -- ch. 7. The environmental benefits and costs of genetically modified (GM) crops / Justus Wesseler, Sara Scatasta, El Hadji Fall -- ch. 8. Coexistence of genetically modified (GM) and non-modified (non GM) crops : are the two main property rights regimes equivalent with respect to the coexistence value? / Volker Beckmann, Claudio Soregaroli, Justus Wesseler -- ch. 9. Biotechnology and biofuel / Steven E. Sexton, David Zilberman -- ch. 10. Consumer preferences for genetically modified food / Jayson L. Lusk -- ch. 11. The effect of GM labeling regime on market outcomes / Elise Golan, Fred Kuchler -- ch. 12. International trade and the welfare effects of biotechnology innovations : GM food crops in Bangladesh, India, Indonesia, and the Philippines / Guillaume P. Grue, Antoine Bou$1#0B(B, Simon Mevel -- ch. 13. Global welfare and trade-related regulations of GM food : biosafety, markets, and politics / Alan Randall -- ch. 14. Innovation, risk, precaution, and the regulation of GM crops / Alan Randall.s
Includes index.
Mode of access: World Wide Web.
Keywords: Genetically modified foods; Public welfare